Low‐density extraction solvent based solvent‐terminated dispersive liquid–liquid microextraction for quantitative determination of ionizable pesticides in environmental waters. Issue 6 (4th March 2013) - Tolcha, Teshome; Merdassa, Yared; Megersa, Negussie
<x xml:space="preserve">Abstract</x> A rapid, efficient, and new solvent terminated dispersive liquid–liquid microextraction technique coupled with HPLC was developed for selective extraction and analysis of s‐triazine herbicides from environmental water samples. Important parameters influencing the extraction process including type and volume of extraction and disperser solvent, extraction time, sample pH, ionic strength, and extraction temperature were successfully optimized. Under the optimal conditions, there are excellent linear relationships between the analytical results and concentration in the range of 10–400 mg/L for atrazine, propazine, prometryn, and terbutryn. LOD and LOQ ranged from 0.60 to 2.33 μg/L and 2.0 to 7.7 μg/L, respectively. Performance of the analytical technique was evaluated by carrying out the repeatability and reproducibility analyses that were ranged from 2.86 to 5.66% and 4.64 to 5.89% for 100 μg/L of each target analyte, respectively. The proposed method has been successfully applied to the analysis of real water samples and acceptable relative recoveries over the range of 65.93–101.46%, with RSDs ≤ 8.80%, were obtained. The overall results have been compared with the literature values. Thus, the method developed could efficiently be used for selective extraction of the target analytes from complex matrices, particularly environmental waters.